Quorum-Quenching Bacteria Isolated From Red Sea Sediments Reduce Biofilm Formation by Pseudomonas aeruginosa - Rehman, Zahid Ur; Leiknes, TorOve (Frontiers in Microbiology, 2018)
Quorum sensing (QS) is the process by which bacteria communicate with each other through small signaling molecules, such as N-acylhomoserine lactones (AHLs). Also, certain bacteria have the ability to degrade AHL molecules by a process referred to as quorum quenching (QQ); therefore, QQ can be used to control bacterial infections and biofilm formation. In this study, we aimed to identify new species of bacteria with QQ activities. To achieve this, Red Sea sediments were collected either in the close vicinity of Sea grass or from area with no vegetation. From these samples, we isolated 72 bacterial strains and tested for their ability to degrade/inactivate AHL molecules. Chromobacterium violaceum CV026 based bioassay was used in initial screening of isolates for QQ activity. The QQ activity of the positive isolates was further confirmed and quantified by employing high-performance liquid chromatography tandem mass spectrometry. These analyses showed that isolated bacterial strain could degrade AHL molecules with different acyl chain length and modifications. Sequencing of 16S-rRNA genes of positive QQ isolates revealed that they belong to three different genera. Specifically, two isolates belong to genus Erythrobacter, four to Labrenzia and one isolate belongs to Bacterioplanes. The genome of one isolate representative of each genus was sequenced and potential QQ enzymes, lactonases and acylases were identified. The ability of these isolates to degrade 3OXO-C12AHLs produced by Pseudomonas aeruginosa PAO1 and hence inhibition of biofilm formation was also investigated. Our results showed that isolate VG12 belonging to genus Labrenzia is better than other isolates at controlling biofilm formation by PAO1and degradation of variety of AHL molecules. Time-course AHL degradation experiment showed that isolate VG1 belonging to genus Erythrobacter could degrade AHLs faster than other isolates. Based on our results it is suggested that QQ bacteria or enzymes can be used in combination with anti-bacterials to overcome resistance against antibiotics.